Economic viability of urban greening as a climate change adaptation measure in cool-climate cities - Suomi, Juuso; Hyyrynen, Matti; Käyhkö, Janina; Käyhkö, Jukka; Juhola, Sirkku (Springer Science and Business Media LLC, 2025)
This study explores whether urban greening through tree planting is an economically viable climate change adaptation measure in Northern Europe's climate. The analysis was conducted by modelling how increased tree canopy cover affects the urban heat island (UHI) effect and, in turn, reduces heatwave-related mortality among vulnerable populations. Using modelling data from 2022 to 2100 for three Finnish cities-Helsinki, Turku, and Oulu-the results suggest that, in some cases, tree planting can be an economically viable adaptation measure to reduce heat-related deaths. This requires that greening is applied in the most densely populated areas of the city. Among the three cities, greening proves most economically viable in Helsinki, which has the highest population density of the three study cities. Conversely, it is not an economically viable adaptation option in Oulu, the study's northernmost and least densely populated city. The effectiveness of greening in economic terms varies depending on the city, the specific climate change scenario, and the intensity of the greening effort. As a result, the net present value (NPV) of tree planting may be either positive or negative. Therefore, any greening initiative should be carefully evaluated within its local context.